The historical school of historians of the Mongol state is a historical study - عميران سناء; غادة حسن (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
During more than three centuries, the Islamic world was subjected to many Crusades that led to the emergence of several emirates in it. The situation continued as it was until Saladin came and fought a series of wars to repel the threat of the Crusaders and was able to achieve his famous victory over them in the Battle of Hattin. After that, the Islamic Levant was exposed to the Mongolian invasion, which destroyed many Islamic cities, spread devastation in them, and took control of the region politically, economically, and culturally. After the Mongols took over the Khwarezmian state, they attacked Baghdad and ended the Abbasid Caliphate there in the year 656 AH/1258 AD. As a result of this Mongol invasion, many historians began to record the events that took place and presented several books that dealt with the facts and topics of that period and the changes that occurred because of this invasion politically, economically, socially, and culturally. Among the most famous of these historians are: Ibn al-Atheer, Abd al-Latif al-Baghdadi, Yaqut al-Hamawi, Ata Malik al-Juwayni, and Rashid Fadlallah. Al-Hamdhani and others. This research will discuss these historians and their approach to writing history.